A hybrid optimization technique for solving economic dispatch problem - Mansor M.H.; Raja Kechek R.M.S.; Musirin I.; Rahmat N.A.; Rahman M.S.A.; Roslan N.; Abdullah M.N.; Shaaya S.A.; Aziz N.F.A. (Institute of Physics Publishing, 2023)
Computer programming; Costs; Heuristic methods; Optimization; Problem solving; Scheduling; Artificial Immune System; Economic dispatch problems; Meta-heuristic techniques; Operational planning; Optimization techniques; Population-based optimization; Power system engineers; Total production cost; Electric load dispatching